2004
DOI: 10.1098/rsbl.2003.0137
|View full text |Cite
|
Sign up to set email alerts
|

Increased fecundity associated with infection by a Cytophaga –like intracellular bacterium in the predatory mite, Metaseiulus occidentalis

Abstract: The endosymbiont Wolbachia has gained widespread notoriety over the past decade because of its high infection frequency among arthropods, and the unique heterogeneity of the host reproductive effects that it has been implicated as causing to enhance its own spread. Recently, another endosymbiotic bacterium from the Cytophaga-FlavobacteriumBacteroides phylum has been shown to be widespread among arthropods and manipulate its hosts' reproduction to enhance its own spread. We show that infection by this Cytophaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 13 publications
3
68
0
1
Order By: Relevance
“…Wasps that had only Cardinium survived 40% longer, which in turn resulted in 50% more male offspring production than cured wasps. Other studies have found fecundity benefits associated with Cardinium in mites (Weeks and Stouthamer, 2004), but this is the first instance in which adult survivorship has been shown to be positively associated with Cardinium infection. The mechanism by which adult longevity is increased is not clear, but it is possible that increased survivorship in Cardinium-infected wasps may be directly attributable to decreased egg load.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Wasps that had only Cardinium survived 40% longer, which in turn resulted in 50% more male offspring production than cured wasps. Other studies have found fecundity benefits associated with Cardinium in mites (Weeks and Stouthamer, 2004), but this is the first instance in which adult survivorship has been shown to be positively associated with Cardinium infection. The mechanism by which adult longevity is increased is not clear, but it is possible that increased survivorship in Cardinium-infected wasps may be directly attributable to decreased egg load.…”
Section: Discussionmentioning
confidence: 61%
“…Theory suggests that maternally inherited endosymbionts can promote their spread and persistence in host populations by enhancing the production of daughters relative to uninfected individuals in the population (Caspari and Watson, 1959;Turelli, 1994;Werren, 1997). This can be accomplished by providing a net fitness benefit to infected individuals, increasing their survival and/or fecundity, and thereby increasing female offspring production (Weeks and Stouthamer, 2004). Other symbionts are only beneficial under some conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In a few other arthorpods and in all nematodes, Wolbachia is obligatory, and thus required for host fertility (Bandi et al, 2001;Pannebakker et al, 2007). Cardinium is known to increase fecundity in Metaseiulus occidentalis (Weeks and Stouthamer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Cardinium could be involved in oogenesis as well as in embryogenesis and larval development. For instance, Cardinium infection is associated with an increase of fecundity in a mite host (Weeks and Stouthamer, 2004). In other examples, the reproductive manipulator Wolbachia is necessary for oogenesis in a parasitic wasp (Dedeine et al, 2001) and for normal development of eggs in the vine weevil (Son et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Like Wolbachia, in the a-Proteobacteria, Cardinium may cause manipulation of host reproduction in ways that increase its frequency within a host population, including feminization (genotypic males develop as functional phenotypic females) (Weeks et al, 2001), cytoplasmic incompatibility (Hunter et al, 2003;Gotoh et al, 2007) and thelytokous parthenogenesis (females produce only daughters from unfertilized eggs) (Zchori-Fein et al, 2001, 2004Provencher et al, 2005;Groot and Breeuwer, 2006;Matalon et al, 2007). Cardinium also increases the fecundity of a mite host (Weeks and Stouthamer, 2004).…”
Section: Introductionmentioning
confidence: 99%